Propriedades anticâncer da fenstatina, 4-metoxifenil-3,4,5-trimetoxifenilmetanona (RR07) - Magalhães, Hemerson Iury Ferreira (2009)
The phenstatin, chemically known as 4-methoxyphenyl-3,4,5-trimetoxiphenylmethane, was called in the present study as RR07. This compound is a bisarylketone with stilbenoid skeleton obtained from combretastatin A4, with recognized cytotoxic and antineoplasic activities. Then, a detailed study of RR07 anticancer properties was conducted in several biological models. The cytotoxic activity of eleven compounds (RR01, RR02, RR03, RR04, RR05, RR06, RR07, RR08, RR09, RR10, RR11) was determined against thirteen tumor cell lines by MTT assay. Structure-activity relationship pointed out that the presence of ring A (3,4,5-trimethoxiphenyl) is essential for the cytotoxic potential. The RR07 was one of the most cytotoxic compounds, showing IC50 values ranging from 0.009 to 17.49 µM. Investigations on mechanism of action (0.25, 0.50, 1.00, 2.00 and 4.00 µM) showed a concentration-dependent manner cell viability reduction (trypan blue dye exclusion test) and proliferation decreasing (BrdU assay). Morphological alterations determined by hematoxylin/eosin and acridine orange/ethidium bromide fluorescent double staining methods indicated an increased number of apoptotic cells at lowest concentrations (0.25 and 0.50 µM) and necrotic cells at higher concentrations (1.00, 2.00 and 4.00 µM). Flow cytometry analyses showed that RR07 induced DNA fragmentation and cell cycle arrest at G2/M starting at 0.25 µM. In the comet assay performed with human peripheral blood mononuclear cells (PBMC), RR07 caused DNA strand breaks only at higher concentrations (2.00 and 4.00 µM). Experiments with isolated tubulin, RR07 also induced tubulin polymerization inhibition in a concentration of 10 μM. In vivo antitumor experiments showed that Sarcoma 180 transplanted-mice treated with RR07 intraperitoneally (ip) presented a tumor growth inhibition ratios of 30.9% and 48.19% (20 mg/kg/day and 40 mg/kg/day, respectively) and inhibition of 55.68% in associated treatment (5-Fluoruracil 10 mg/kg/day + RR07 20 mg/kg/day). Histopathological analyses of kidneys, spleen and livers revealed incipient and reversible alterations. In summary, RR07 can be considered as a pharmacological useful tool as well as a lead molecule to obtain novel compounds with low toxicity and promising antitumor properties.